?
Periodic and Aperiodic Discrete-Time Sinusoids
x
(
n
)
=
A
c
o
s
[
2
π
f
0
n
]
=
x
(
n
+
N
)
=
A
c
o
s
[
2
π
f
0
(
n
+
N
)
]
=
A
c
o
s
[
2
π
f
0
n
+
2
π
f
0
N
]
x(n)=Acos[2 \pi f_0 n]=x(n+N)=Acos[2 \pi f_0 (n+N)]=Acos[2 \pi f_0 n+2 \pi f_0 N]
x(n)=Acos[2πf0?n]=x(n+N)=Acos[2πf0?(n+N)]=Acos[2πf0?n+2πf0?N]
2
π
f
0
N
=
2
π
k
2\pi f_0 N =2 \pi k
2πf0?N=2πk just
f
0
=
k
N
f_0 = \frac{k}{N}
f0?=Nk?
n is integer: Periodic
n is not integer: Aperiodic
Periodic judgment of composite signals
Find N for each signal
if N 1 N 2 = r a t i o n a l ? n u m b e r \frac{N_1}{N_2} = rational \ number N2?N1??=rational?number it is Periodic
Find the lowest common multiple($ LCM(N_1,N_2)$)
Periodic is L C M ( N 1 , N 2 ) LCM(N_1,N_2) LCM(N1?,N2?)
Odd and even signals
odd: x 0 ( t ) = 1 2 [ x ( t ) ? x ( ? t ) ] x_0(t)=\frac{1}{2}[x(t)-x(-t)] x0?(t)=21?[x(t)?x(?t)]
even: x e ( t ) = 1 2 [ x ( t ) + x ( ? t ) ] x_e(t) = \frac{1}{2}[x(t)+x(-t)] xe?(t)=21?[x(t)+x(?t)]
x ( t ) = x 0 ( t ) + x e ( t ) x(t) = x_0(t) + x_e(t) x(t)=x0?(t)+xe?(t)
energy signal and power signal
energy: E = ∑ n = ? ∞ ∞ ∣ x [ n ] ∣ 2 E=\sum_{n=-\infty}^{\infty}|x[n]|^2 E=∑n=?∞∞?∣x[n]∣2
power:
Periodic: P ∞ = lim ? N → ∞ 1 2 N + 1 ∑ n = ? ∞ + ∞ ∣ x [ n ] ∣ 2 P_\infty=\lim_{N\to\infty}\frac1{2N+1}\sum_{n=-\infty}^{+\infty}|x[n]|^2 P∞?=limN→∞?2N+11?∑n=?∞+∞?∣x[n]∣2
Aperiodic: P x = 1 N ∑ n = 0 N ? 1 ∣ x [ n ] ∣ 2 P_x=\frac1{N}\sum_{n=0}^{N-1}|x[n]|^2 Px?=N1?∑n=0N?1?∣x[n]∣2
energy signal:energy is finite,power is zero
power signal:energy is infinite,power is finite
?
find the energy and power for
?
?
Linear systems and nonlinear systems
Causal and Acausal Systems
Time-varying and time-invariant systems
static system and dynamic system
Stable and unstable systems
convolution
convolution sum
circular convolution
Stability of linear time-invariant systems
Must have: x ( n ) = y ( n ) = 0 x(n) = y(n) = 0 x(n)=y(n)=0
Four steps to solve problems:
if y4 = y3 ,the system is linear
?
casual system: The output depends only on present and past signals
Acausal Systems:The output depends on at least one future input
eg:Y(n) = x(-n) is non-casual (at n = -1)
even and odd is non-casual
ps: anti-casual system: output only upon “only future input” for all time
?
Time-varying system(TVS):
y(n) = F[x(n)] = x(n)cos(2 w π w \pi wπn)
y(n,k) = F[x(n-k)] = x(n-k)cos(2 w π w \pi wπn)
y(n-k) ≠ \ne = y(n,k)
y(n) to y(n,k):only change n for x(n)
time-invariant systems :
y(n,k) = y(n-k)
eg:y(n-k) = sin (x(n-k))
y change n for all n
?
static system (memory-less system):
output only depends on now input for all time
dynamic system:
output depends on past and/or future inputs
?
Stable system: BIBO
bounded input to bounded output
unstable systems:
bounded input to unbounded output
eg: y ( n ) = y 2 ( n ? 1 ) + 2 δ ( n ) y(n)=y^2(n-1)+2\delta (n) y(n)=y2(n?1)+2δ(n)
?
y ( n ) = ∑ k = ? ∞ ∞ x ( k ) h ( n ? k ) y(n)=\sum_{k=-\infty}^{\infty}x(k)h(n-k) y(n)=∑k=?∞∞?x(k)h(n?k)
y ( n ) = x ( n ) ? h ( n ) y(n)=x(n)*h(n) y(n)=x(n)?h(n)
matrix method:
x(n) = {1,2,3,4} h(n)={0,2,2,2}
length of x(n):4 samples;k
length of h(n):4 samples;m
length of y(n): = k + m - 1 = 4 + 4 - 1 = 7 samples
?
x(n) = {2,1,2} h(n) = {1,2,3}
y ( n ) = ∑ k = ? ∞ ∞ x ( k ) h ( n ? k ) y(n)=\sum_{k=-\infty}^{\infty}x(k)h(n-k) y(n)=∑k=?∞∞?x(k)h(n?k)
?
S = ∑ k = ? ∞ ∞ ∣ h ( n ) ∣ < ∞ S=\sum_{k=-\infty}^{\infty}|h(n)| < \infty S=∑k=?∞∞?∣h(n)∣<∞
it is stability
eg: h ( n ) = ( 0.8 ) n u ( n + 2 ) h(n) = (0.8)^n u(n+2) h(n)=(0.8)nu(n+2)
?
Condition for existence of Fourier Series
period function:
f ( x ) = a 0 + ∑ n = 1 ∞ ( a n c o s ( n w 0 t ) + b n s i n ( n w 0 t ) f(x)=a_0+\sum_{n=1}^\infty(a_ncos(nw_0t)+b_n sin(nw_0t) f(x)=a0?+∑n=1∞?(an?cos(nw0?t)+bn?sin(nw0?t)
a 0 = 1 T 1 ∫ 0 T 1 f ( t ) d t a_{0}=\frac{1}{T_{1}}\int_{0}^{T_1}f(t)dt a0?=T1?1?∫0T1??f(t)dt
a n = 2 T 1 ∫ 0 T 1 f ( t ) cos ? n w 1 t d t a_{n}=\frac{2}{T_{1}}\int_{0}^{T_{1}}f(t)\cos nw_1tdt an?=T1?2?∫0T1??f(t)cosnw1?tdt
b n = 2 T 1 ∫ 0 T 1 f ( t ) sin ? n w 1 t d t b_{n}=\frac{2}{T_{1}}\int_{0}^{T_{1}}f(t)\sin nw_1tdt bn?=T1?2?∫0T1??f(t)sinnw1?tdt
eg:
?
x n = ∑ k = 0 N ? 1 c ( k ) e J k 2 π N n x_n=\sum_{k=0}^{N-1}c(k)e^{Jk\frac{2\pi }{N}n} xn?=∑k=0N?1?c(k)eJkN2π?n
c ( k ) = 1 N ∑ n = 0 N ? 1 x ( n ) e ? J k 2 π N n c(k)=\frac{1}{N}\sum_{n=0}^{N-1}x(n)e^{-Jk\frac{2\pi}{N}n} c(k)=N1?∑n=0N?1?x(n)e?JkN2π?n
?
x ( w ) = ∫ ? ∞ + ∞ x ( t ) e ? J w t d t x(w)=\int_{-\infty}^{+\infty}x(t)e^{-Jwt}dt x(w)=∫?∞+∞?x(t)e?Jwtdt
Inverse transformation: x ( t ) = 1 2 π ∫ ? ∞ + ∞ x ( w ) e j w t d w x(t)=\frac{1}{2\pi}\int_{-\infty}^{+\infty}x(w)e^{jwt}dw x(t)=2π1?∫?∞+∞?x(w)ejwtdw
?
properties of CTFT
Parseval’s Theorem
Any signal is built up addition of elementary signals which are at different frequencies.
CTFT is used to transform the signal from time domain to frequency domain.
With the help of CTFT,plot the amplitude and phase spectrum.
CTFT can be efxpressed as:
x ( w ) = ∫ ? ∞ + ∞ x ( t ) e ? J w t d t x(w)=\int_{-\infty}^{+\infty}x(t)e^{-Jwt}dt x(w)=∫?∞+∞?x(t)e?Jwtdt
Inverse transformation: x ( t ) = 1 2 π ∫ ? ∞ + ∞ x ( w ) e j w t d w x(t)=\frac{1}{2\pi}\int_{-\infty}^{+\infty}x(w)e^{jwt}dw x(t)=2π1?∫?∞+∞?x(w)ejwtdw
?
These conditions are sufficient but not necessary Condition.
If the conditions are not met, there is not necessarily no Fourier transform.
?
?
Inverse transformation for function
important
?
F [ f ( t ) ] = F ( ω ) , F [ g ( t ) ] = G ( ω ) \mathscr{F}[f(t)]=F(\omega),\quad\mathscr{F}[g(t)]=G(\omega) F[f(t)]=F(ω),F[g(t)]=G(ω)
F [ α f ( t ) + β g ( t ) ] = α F ( ω ) + β G ( ω ) F ? 1 [ α F ( ω ) + β G ( ω ) ] = α f ( t ) + β g ( t ) \begin{aligned}\mathscr{F}[\alpha f(t)+\beta g(t)]&=\alpha F(\omega)+\beta G(\omega)\\\mathscr{F}^{-1}[\alpha F(\omega)+\beta G(\omega)]&=\alpha f(t)+\beta g(t)\end{aligned} F[αf(t)+βg(t)]F?1[αF(ω)+βG(ω)]?=αF(ω)+βG(ω)=αf(t)+βg(t)?
F [ f ( t ) ] = F ( ω ) \mathcal{F}[f(t)]=F(\omega) F[f(t)]=F(ω)
F [ f ( t ? t 0 ) ] = e ? j ω t 0 F ( ω ) F ? 1 [ F ( ω ? ω 0 ) ] = e j ω 0 t f ( t ) \begin{aligned}\mathscr{F}[f(t-t_0)]&=e^{-j\omega t_0}F(\omega)\\\mathscr{F}^{-1}[F(\omega-\omega_0)]&=e^{j\omega_0t}f(t)\end{aligned} F[f(t?t0?)]F?1[F(ω?ω0?)]?=e?jωt0?F(ω)=ejω0?tf(t)?
F [ f ( t ) ] = F ( ω ) \mathcal{F}[f(t)]=F(\omega) F[f(t)]=F(ω)
F [ f ( a t ) ] = 1 ∣ a ∣ F ( ω a ) \mathscr{F}[f(at)]=\frac{1}{|a|}F\left(\frac{\omega}{a}\right) F[f(at)]=∣a∣1?F(aω?)
F [ f ( t ) ] = F ( ω ) \mathcal{F}[f(t)]=F(\omega) F[f(t)]=F(ω)
F [ f ( t ) e j w 0 t ] = F ( ω ? ω 0 ) F ? 1 [ f ( t ) e ? j w 0 t ] = F ( ω + ω 0 ) \begin{aligned}\mathscr{F}[f(t)e^{jw_0t}]&=F(\omega - \omega_0)\\\mathscr{F}^{-1}[f(t)e^{-jw_0t}]&=F(\omega + \omega_0)\end{aligned} F[f(t)ejw0?t]F?1[f(t)e?jw0?t]?=F(ω?ω0?)=F(ω+ω0?)?
F [ f ( t ) ] = F ( ω ) \mathcal{F}[f(t)]=F(\omega) F[f(t)]=F(ω)
F [ d n f ( t ) d t n ] = ( j ω ) n F ( ω ) F ? 1 [ d n F ( ω ) d ω n ] = ( ? j t ) n f ( t ) \begin{gathered} \mathscr{F}\left[\frac{d^{n}f(t)}{dt^{n}}\right]=(j\omega)^{n}F(\omega) \\ \mathscr{F}^{-1}\left[\frac{d^{n}F(\omega)}{d\omega^{n}}\right]=(-jt)^{n}f(t) \end{gathered} F[dtndnf(t)?]=(jω)nF(ω)F?1[dωndnF(ω)?]=(?jt)nf(t)?
F [ f ( t ) ] = F ( ω ) \mathcal{F}[f(t)]=F(\omega) F[f(t)]=F(ω)
F [ ( ? j t ) n f ( t ) ] = d n F ( w ) d w n \mathscr{F} [(-jt)^{n}f(t)]= \frac{d^{n}F(w)}{dw^{n}} F[(?jt)nf(t)]=dwndnF(w)?
F [ t f ( t ) ] = j d F ( w ) d w \mathscr{F} [tf(t)]= j\frac{dF(w)}{dw} F[tf(t)]=jdwdF(w)?
F [ f ( t ) ] = F ( ω ) , F [ g ( t ) ] = G ( ω ) \mathscr{F}[f(t)]=F(\omega),\quad\mathscr{F}[g(t)]=G(\omega) F[f(t)]=F(ω),F[g(t)]=G(ω)
F [ f 1 ( t ) ? f 2 ( t ) ] = F 1 ( ω ) ? F 2 ( ω ) \mathscr{F}[f_1(t) *f_2(t)]=F_1(\omega)·F_2(\omega) F[f1?(t)?f2?(t)]=F1?(ω)?F2?(ω)
F [ f 1 ( t ) ? f 2 ( t ) ] = 1 2 π F 1 ( ω ) ? F 2 ( ω ) \mathscr{F}[f_1(t) ·f_2(t)]=\frac{1}{2\pi}F_1(\omega)*F_2(\omega) F[f1?(t)?f2?(t)]=2π1?F1?(ω)?F2?(ω)
?
if x(t) CTFT to x ( w ) x(w) x(w) or x ( f ) x(f) x(f)
E = ∫ ? ∞ ∞ ∣ x ( t ) ∣ 2 d t = ∫ ? ∞ ∞ ∣ x ( f ) ∣ 2 d f E=\int_{-\infty}^{\infty}|x(t)|^{2}dt=\int_{-\infty}^{\infty}|x(f)|^{2}df E=∫?∞∞?∣x(t)∣2dt=∫?∞∞?∣x(f)∣2df
?
F [ e j ω 0 t ] = 2 π δ ( ω ? ω 0 ) F [ e ? j ω 0 t ] = 2 π δ ( ω + ω 0 ) \begin{aligned}\mathscr{F}[e^{j\omega_0t}]&=2\pi\delta(\omega-\omega_0)\\\mathscr{F}[e^{-j\omega_0t}]&=2\pi\delta(\omega+\omega_0)\end{aligned} F[ejω0?t]F[e?jω0?t]?=2πδ(ω?ω0?)=2πδ(ω+ω0?)?
?
F [ cos ? ( ω 0 t ) ] = F [ e j ω 0 t + e ? j ω 0 t 2 ] = π [ δ ( ω ? ω 0 ) + δ ( ω + ω 0 ) ] F [ sin ? ( ω 0 t ) ] = F [ e j ω 0 t ? e ? j ω 0 t 2 j ] = j π [ δ ( ω + ω 0 ) ? δ ( ω ? ω 0 ) ] \begin{gathered} \mathscr{F}[\cos(\omega_{0}t)]=\mathscr{F}[\frac{e^{j\omega_{0}t}+e^{-j\omega_{0}t}}{2}]=\pi[\delta(\omega-\omega_{0})+\delta(\omega+\omega_{0})] \\ \mathscr{F}[\sin(\omega_{0}t)]=\mathscr{F}[\frac{e^{j\omega_{0}t}-e^{-j\omega_{0}t}}{2j}]=j\pi[\delta(\omega+\omega_{0})-\delta(\omega-\omega_{0})] \end{gathered} F[cos(ω0?t)]=F[2ejω0?t+e?jω0?t?]=π[δ(ω?ω0?)+δ(ω+ω0?)]F[sin(ω0?t)]=F[2jejω0?t?e?jω0?t?]=jπ[δ(ω+ω0?)?δ(ω?ω0?)]?
?
f ( t ) = ∑ n = ? ∞ ∞ F ( n w 0 ) e j n w 0 t f(t)=\sum_{n=-\infty}^{\infty}F(nw_0)e^{jnw_0 t} f(t)=∑n=?∞∞?F(nw0?)ejnw0?t
F ( w ) = F [ f ( t ) ] = 2 π ∑ n = ? ∞ ∞ F ( n w 0 ) δ ( ω ? n ω 0 ) F(w) = \mathscr{F}[f(t)] = 2\pi \sum_{n=-\infty}^{\infty}F(nw_0)\delta(\omega-n\omega_{0}) F(w)=F[f(t)]=2π∑n=?∞∞?F(nw0?)δ(ω?nω0?)
F ( n w 1 ) = 1 T ∫ 0 T f ( t ) e ? j n w 0 t d t F(nw_1) = \frac{1}{T}\int_{0}^{T} f(t)e^{-jnw_0t}dt F(nw1?)=T1?∫0T?f(t)e?jnw0?tdt
?
DTFT: X ( e j ω ) = ∑ n = ? ∞ + ∞ x [ n ] e ? j ω n X\left(e^{j\omega}\right)=\sum_{n=-\infty}^{+\infty}x[n]e^{-j\omega n} X(ejω)=∑n=?∞+∞?x[n]e?jωn
Inverse transform of DTFT: x [ n ] = 1 2 π ∫ 2 π X ( e j ω ) e j ω n d ω x\left[n\right]=\frac1{2\pi}\int_{2\pi}X(e^{j\omega})e^{j\omega n}d\omega x[n]=2π1?∫2π?X(ejω)ejωndω
x ( n ) = a n u ( n ) ; ∣ a ∣ < 1 x(n) = a^n u(n);|a|<1 x(n)=anu(n);∣a∣<1
DTFT?[X(n)] = ∑ n = ? ∞ ∞ x ( n ) e ? j w n = ∑ n = 0 + ∞ a n e ? j w n = ∑ n = 0 + ∞ ( a ? e ? j w ) n = 1 1 ? a e ? j w = 1 1 ? a ( c o s w ? j s i n w ) = 1 ( 1 ? a c o s w ) + j a s i n w \begin{aligned}\text{DTFT [X(n)]}&=\sum_{n=-\infty}^{\infty}x({n})e^{-jwn}\\&=\sum_{n=0}^{+\infty}a^ne^{-jwn}\\&=\sum_{n=0}^{+\infty}(a\cdot e^{-jw})^n\\&=\frac1{1-ae^{-jw}} \\&=\frac{1}{1-a(cosw-jsinw)} \\&=\frac{1}{(1-acosw)+jasinw}\end{aligned} DTFT?[X(n)]?=n=?∞∑∞?x(n)e?jwn=n=0∑+∞?ane?jwn=n=0∑+∞?(a?e?jw)n=1?ae?jw1?=1?a(cosw?jsinw)1?=(1?acosw)+jasinw1??
magnitude:
∣ x ( e j w ) ∣ = 1 ( 1 ? a c o s w ) 2 + ( a s i n w ) 2 = 1 1 + a 2 ? 2 a c o s w |x(e^{jw})| = \frac{1}{\sqrt{(1-acosw)^2}+(asinw)^2 }=\frac{1}{\sqrt{1+a^2-2acosw} } ∣x(ejw)∣=(1?acosw)2?+(asinw)21?=1+a2?2acosw?1?
phase:
∠ x ( e j w ) = ? a r c t a n a s i n w 1 ? a c o s w \angle x(e^{jw}) = -arctan\frac{asinw}{1-acosw} ∠x(ejw)=?arctan1?acoswasinw?
eg:x(n) = {-4,3,-2,3,-4}
find:(1). x ( e j 0 ) x(e^{j0}) x(ej0) (2). x ( e j w ) x(e^{jw}) x(ejw) (3). ∫ π ? π x ( e j w ) d w \int_{\pi }^{-\pi} x(e^ {jw} )dw ∫π?π?x(ejw)dw
?
a x 1 [ n ] + b x 2 [ n ] ? a X 1 ( e j ω ) + b X 2 ( e j ω ) ax_1\left[n\right]+bx_2\left[n\right]\leftrightarrow aX_1(e^{j\omega})+bX_2(e^{j\omega}) ax1?[n]+bx2?[n]?aX1?(ejω)+bX2?(ejω)
x ( n ) ? x ( e j w ) x(n) \leftrightarrow x(e^{jw}) x(n)?x(ejw)
x ( n ? n 0 ) ? x ( e j w ) ? e ? j w n 0 x( n - n_0) \leftrightarrow x(e^{jw})·e^{-jwn_0} x(n?n0?)?x(ejw)?e?jwn0?
x ( n ) ? x ( e j w ) x(n) \leftrightarrow x(e^{jw}) x(n)?x(ejw)
x ( n ) ? e ? j w n 0 ? x ( e j ( w ? w 0 ) ) x(n)·e^{-jwn_0} \leftrightarrow x(e^{j(w-w_0)}) x(n)?e?jwn0??x(ej(w?w0?))
x ( n ) ? x ( e j w ) x(n) \leftrightarrow x(e^{jw}) x(n)?x(ejw)
n x ( n ) ? j d x ( e j w ) d w n x(n) \leftrightarrow j \frac{dx(e^{jw})}{dw} nx(n)?jdwdx(ejw)?
?
eg:
1. y ( n ) ? A y ( n ? 1 ) = x ( n ) ; ∣ A ∣ < 1 y(n) - Ay(n-1) = x(n);|A|<1 y(n)?Ay(n?1)=x(n);∣A∣<1
2. y ( n ) ? 3 4 y ( n ? 1 ) + 1 8 y ( n ? 2 ) = 2 x ( n ) y(n) - \frac{3}{4}y(n-1)+\frac{1}{8}y(n-2)=2x(n) y(n)?43?y(n?1)+81?y(n?2)=2x(n)
3. x ( e j w ) = e ? j w x(e^{jw})=e^{-jw} x(ejw)=e?jw for ? π ≤ w ≤ π -\pi \le w \le \pi ?π≤w≤π
4.find convolution x ( n ) = 1 2 n u ( n ) x(n) = \frac{1}{2}^n u(n) x(n)=21?nu(n) and x ( n ) = 1 3 n u ( n ) x(n) = \frac{1}{3}^n u(n) x(n)=31?nu(n)
?
DFT is equally spaced sampling of DTFT
DFT: x ( n ) —— > x ( k ) x(n) ——> x(k) x(n)——>x(k)
x ( k ) = ∑ n = 0 N ? 1 x ( n ) e ? j 2 π k N n ; k = 0 , 1 , 2 , 3 , . . . , N ? 1 x(k) = \sum_{n=0}^{N-1}x(n)e^{-j\frac{2\pi k}{N}n};k=0,1,2,3,...,N-1 x(k)=∑n=0N?1?x(n)e?jN2πk?n;k=0,1,2,3,...,N?1
making W N = e ? j 2 π N W_N = e^{-j\frac{2\pi}{N}} WN?=e?jN2π?
x ( k ) = ∑ n = 0 N ? 1 x ( n ) W N k n x(k) = \sum_{n=0}^{N-1}x(n)W_N^{kn} x(k)=∑n=0N?1?x(n)WNkn?
?
eg: x ( k ) = ∑ n = 0 4 ? 1 x ( n ) e ? j 2 π k 4 n x(k) = \sum_{n=0}^{4-1}x(n)e^{-j\frac{2\pi k}{4}n} x(k)=∑n=04?1?x(n)e?j42πk?n
1. x ( k ) = ∑ n = 0 N ? 1 x ( n ) e ? j 2 π k N n ; k = 0 , 1 , 2 , 3 , . . . , N ? 1 x(k) = \sum_{n=0}^{N-1}x(n)e^{-j\frac{2\pi k}{N}n};k=0,1,2,3,...,N-1 x(k)=∑n=0N?1?x(n)e?jN2πk?n;k=0,1,2,3,...,N?1
2.matrix method
?
X 1 ( k ) = D F T [ x 1 ( n ) ] X_1(k)=DFT[x_1(n)] X1?(k)=DFT[x1?(n)]
X 2 ( k ) = D F T [ x 2 ( n ) ] X_2(k)=DFT[x_2(n)] X2?(k)=DFT[x2?(n)]
D F T [ a x 1 ( n ) + b x 2 ( n ) ] = a X 1 ( k ) + b X 2 ( k ) DFT[ax_1(n)+bx_2(n)]=aX_1(k)+bX_2(k) DFT[ax1?(n)+bx2?(n)]=aX1?(k)+bX2?(k)
DFT: x [ n ] ? h [ n ] ? X [ k ] ? H [ k ] x[n]\circledast h[n]\Leftrightarrow X[k]·H[k] x[n]?h[n]?X[k]?H[k]
DFT: x [ n ] ? h [ n ] ? X [ k ] ? H [ k ] x[n]· h[n]\Leftrightarrow X[k]\circledast H[k] x[n]?h[n]?X[k]?H[k]
D F T [ x ( n ) ] = x ( k ) DFT[x(n)] = x(k) DFT[x(n)]=x(k)
x ( n + N ) = x ( n ) x(n+N) = x(n) x(n+N)=x(n);for all n
x ( k + N ) = x ( k ) x(k+N) = x(k) x(k+N)=x(k);for all k
D F T [ x ( n ) e j 2 π N l n ] = x ( ( k ? l ) ) N DFT[x(n)e^{j\frac{2\pi}{N}ln}]=x((k-l))_N DFT[x(n)ejN2π?ln]=x((k?l))N?
(( )) is cyclic frequency
?
[ y ( n ) = x ( n ) ? h ( n ) ] [y(n) = x(n)*h(n)] [y(n)=x(n)?h(n)]
then the length of x(n) is L,and h(n) is M
the length of linear convolution: N = L + M -1
?
[ y ( n ) = x ( n ) ? h ( n ) ] [y(n) = x(n)\circledast h(n)] [y(n)=x(n)?h(n)]
then the length of x(n) is L,and h(n) is M(add 0)
the length of cyclical convolution is :N = max(L,M)
?
then the length of x k ( n ) x_k(n) xk?(n) ( x k ( n ) x_k(n) xk?(n) is not x ( n ) x(n) x(n)) is L,and h(n) is M
the length of convolution is :N = L + M - 1 (the size of N is depend on you)
eg: x ( n ) = { 3 , ? 1 , 0 , 1 , 3 , 2 , 0 , 1 , 2 , 1 } x(n) = \{ 3,-1,0,1,3,2,0,1,2,1\} x(n)={3,?1,0,1,3,2,0,1,2,1} h ( n ) = { 1 , 1 , 1 } h(n) = \{ 1,1,1\} h(n)={1,1,1}
1.we take N = 6,then 6= L + 3 - 1;so L = 4.
x 1 ( n ) = { 0 , 0 , 3 , ? 1 , 0 , 1 } x_1(n) = \{ 0,0,3,-1,0,1 \} x1?(n)={0,0,3,?1,0,1}
x 2 ( n ) = { 0 , 1 , 3 , 2 , 0 , 1 } x_2(n) = \{ 0,1,3,2 ,0,1\} x2?(n)={0,1,3,2,0,1}
x 3 ( n ) = { 0 , 1 , 2 , 1 , 0 , 0 } x_3(n) = \{ 0,1,2,1,0,0 \} x3?(n)={0,1,2,1,0,0}
h ( n ) = { 1 , 1 , 1 , 0 , 0 , 0 } h(n) = \{1,1,1,0,0,0\} h(n)={1,1,1,0,0,0}
2.calculate
x 1 ( n ) ? h ( n ) = { 1 , 1 , 3 , 2 , 2 , 0 } x_1(n)\circledast h(n) =\{1,1,3,2,2,0\} x1?(n)?h(n)={1,1,3,2,2,0}
x 2 ( n ) ? h ( n ) = { 1 , 2 , 4 , 6 , 5 , 3 } x_2(n)\circledast h(n)=\{1,2,4,6,5,3\} x2?(n)?h(n)={1,2,4,6,5,3}
x 3 ( n ) ? h ( n ) = { 0 , 1 , 3 , 4 , 3 , 1 } x_3(n)\circledast h(n) =\{0,1,3,4,3,1\} x3?(n)?h(n)={0,1,3,4,3,1}
3.Remove first (M-1) points ,Concatenate all results
the result is { 3 , 2 , 2 , 0 , 4 , 6 , 5 , 3 , 3 , 4 , 3 , 1 } \{3,2,2,0,4,6,5,3,3,4,3,1\} {3,2,2,0,4,6,5,3,3,4,3,1}
?
then the length of x k ( n ) x_k(n) xk?(n) ( x k ( n ) x_k(n) xk?(n) is not x ( n ) x(n) x(n)) is L,and h(n) is M
the length of convolution is :N = L + M - 1 (the size of N is depend on you)
eg: x ( n ) = { 3 , ? 1 , 0 , 1 , 3 , 2 , 0 , 1 , 2 , 1 } x(n) = \{ 3,-1,0,1,3,2,0,1,2,1\} x(n)={3,?1,0,1,3,2,0,1,2,1} h ( n ) = { 1 , 1 , 1 } h(n) = \{ 1,1,1\} h(n)={1,1,1}
1.we take N = 5,then 5 = L + 3 - 1;so L = 3.
x 1 ( n ) = { 0 , 0 , 3 , ? 1 , 0 } x_1(n) = \{ 0,0,3,-1,0 \} x1?(n)={0,0,3,?1,0}
x 2 ( n ) = { ? 1 , 0 , 1 , 3 , 2 } x_2(n) = \{ -1,0,1,3,2 \} x2?(n)={?1,0,1,3,2}
x 3 ( n ) = { 3 , 2 , 0 , 1 , 2 } x_3(n) = \{ 3,2,0,1,2 \} x3?(n)={3,2,0,1,2}
x 4 ( n ) = { 1 , 2 , 1 , 0 , 0 } x_4(n) = \{ 1,2,1,0,0 \} x4?(n)={1,2,1,0,0}
h ( n ) = { 1 , 1 , 1 , 0 , 0 } h(n) = \{1,1,1,0,0\} h(n)={1,1,1,0,0}
2.calculate
x 1 ( n ) ? h ( n ) = { ? 1 , 0 , 3 , 2 , 2 } x_1(n)\circledast h(n) =\{-1,0,3,2,2\} x1?(n)?h(n)={?1,0,3,2,2}
x 2 ( n ) ? h ( n ) = { 4 , 1 , 0 , 4 , 6 } x_2(n)\circledast h(n)=\{4,1,0,4,6\} x2?(n)?h(n)={4,1,0,4,6}
x 3 ( n ) ? h ( n ) = { 6 , 7 , 5 , 3 , 3 } x_3(n)\circledast h(n) =\{6,7,5,3,3\} x3?(n)?h(n)={6,7,5,3,3}
x 4 ( n ) ? h ( n ) = { 1 , 3 , 4 , 3 , 1 } x_4(n)\circledast h(n) =\{1,3,4,3,1\} x4?(n)?h(n)={1,3,4,3,1}
3.Remove first (M-1) points ,Concatenate all results
the result is { 3 , 2 , 2 , 0 , 4 , 6 , 5 , 3 , 3 , 4 , 3 , 1 } \{3,2,2,0,4,6,5,3,3,4,3,1\} {3,2,2,0,4,6,5,3,3,4,3,1}
?
?
Bilateral Z Transform
Unilateral Z Transform
Bilateral Z Transform:
X ( Z ) = Z { x [ n ] } = ∑ n = ? ∞ + ∞ x [ n ] Z ? n , Z ∈ R x X(Z)=Z\left\{x[n]\right\}=\sum_{n=-\infty}^{+\infty}x\left[n\right]Z^{-n}\text{,}Z\in Rx X(Z)=Z{x[n]}=∑n=?∞+∞?x[n]Z?n,Z∈Rx
Unilateral Z Transform:
X ( Z ) = Z { x [ n ] } = ∑ n = 0 + ∞ x [ n ] Z ? n , Z ∈ R x X(Z)=Z\left\{x[n]\right\}=\sum_{n=0}^{+\infty}x\left[n\right]Z^{-n},Z\in Rx X(Z)=Z{x[n]}=∑n=0+∞?x[n]Z?n,Z∈Rx
?
making z = r ? e j w z = r·e^{jw} z=r?ejw
x ( z ) = ∑ n = ? ∞ ∞ x ( n ) z ? n = ∑ n = ? ∞ ∞ x ( n ) r ? n e ? j w n x(z) = \sum_{n=-\infty}^{\infty}x(n)z^{-n} \\=\sum_{n=-\infty}^{\infty}x(n)r^{-n}e^{-jwn} x(z)=∑n=?∞∞?x(n)z?n=∑n=?∞∞?x(n)r?ne?jwn
if r = 1 r = 1 r=1,then x ( z ) = D T F T x(z) = DTFT x(z)=DTFT
eg: x ( n ) = { 1 , 2 , 3 , 4 , 0 , 1 } x(n) = \{1,2,3,4,0,1 \} x(n)={1,2,3,4,0,1}
x ( z ) = ∑ n = ? ∞ ∞ x ( n ) z ? n = ∑ n = 0 5 x ( n ) z ? n = x ( 0 ) z ? 0 + x ( 1 ) z ? 1 + x ( 2 ) z ? 2 + x ( 3 ) z ? 3 + x ( 4 ) z ? 4 + x ( 5 ) z ? 5 = 1 + 2 z ? 1 + 3 z ? 2 + 4 z ? 3 + z ? 5 x(z) = \sum_{n=-\infty}^{\infty}x(n)z^{-n}=\sum_{n=0}^{5}x(n)z^{-n}=x(0)z^{-0}+x(1)z^{-1}+x(2)z^{-2}+x(3)z^{-3}+x(4)z^{-4}+x(5)z^{-5}\\=1+2z^{-1}+3z^{-2}+4z^{-3}+z^{-5} x(z)=∑n=?∞∞?x(n)z?n=∑n=05?x(n)z?n=x(0)z?0+x(1)z?1+x(2)z?2+x(3)z?3+x(4)z?4+x(5)z?5=1+2z?1+3z?2+4z?3+z?5
ROC:exist entire z-plane except z = 0 z = 0 z=0
using plot:
eg: x ( n ) = { a n ?? ; n ? ≥ 0 0 ?? ; n ? < 0 x(n)=\left\{\begin{matrix} a^n\;;n\ \ge 0 \\ 0\;;n\ < 0 \end{matrix}\right. x(n)={an;n?≥00;n?<0?
x ( z ) = ∑ n = 0 + ∞ ( a z ? 1 ) n = 1 1 ? a z ? 1 = z z ? a x(z) = \sum_{n=0}^{+\infty}(az^{-1})^{n}\\=\frac{1}{1-az^{-1}}=\frac{z}{z-a} x(z)=∑n=0+∞?(az?1)n=1?az?11?=z?az?
needing that : ∣ a z ? 1 ∣ < 1 |az^{-1}|<1 ∣az?1∣<1 just ROC: ∣ z ∣ > ∣ a ∣ |z|> |a| ∣z∣>∣a∣
eg : x ( n ) = ? a n u ( ? n ? 1 ) x(n) = -a^nu(-n-1) x(n)=?anu(?n?1)
ROC: ∣ a ? 1 ∣ < 1 |a^{-1}|<1 ∣a?1∣<1 is just ∣ z ∣ < ∣ a ∣ |z| < |a| ∣z∣<∣a∣
?
x 1 ( n ) ? x 1 ( z ) ; R O C 1 x_1(n) \longrightarrow x_1(z);ROC_1 x1?(n)?x1?(z);ROC1?
x 2 ( n ) ? x 2 ( z ) ; R O C 2 x_2(n) \longrightarrow x_2(z);ROC_2 x2?(n)?x2?(z);ROC2?
a x 1 ( n ) + b x 2 ( n ) ? a x 1 ( z ) + b x 2 ( z ) ; R O C : [ R O C 1 ∩ R O C 2 ] ax_1(n) + bx_2(n) \longrightarrow ax_1(z)+bx_2(z);\\ROC:[ROC_1\cap ROC_2] ax1?(n)+bx2?(n)?ax1?(z)+bx2?(z);ROC:[ROC1?∩ROC2?]
x ( n ) ? x ( z ) x(n) \longrightarrow x(z) x(n)?x(z)
x ( n ? n 0 ) ? x ( z ) z ? n 0 x(n - n_0) \longrightarrow x(z)z^{-n_0} x(n?n0?)?x(z)z?n0?
x ( n ) ? x ( z ) ; R O C : ?? ∣ z ∣ > 1 x(n) \longrightarrow x(z);ROC: \;|z|>1 x(n)?x(z);ROC:∣z∣>1
a n x ( n ) ? x ( z a ) a^nx(n) \longrightarrow x(\frac{z}{a}) anx(n)?x(az?)
x ( n ) ? x ( z ) x(n) \longrightarrow x(z) x(n)?x(z)
n x ( n ) ? ? z d x ( z ) d z nx(n) \longrightarrow -z \frac{dx(z)}{dz} nx(n)??zdzdx(z)?
x 1 ( n ) ? x 2 ( n ) ? x 1 ( z ) ? x 2 ( z ) x_1(n) * x_2(n) \longrightarrow x_1(z)·x_2(z) x1?(n)?x2?(n)?x1?(z)?x2?(z)
x ( 0 ) = lim ? n → 0 x ( n ) = lim ? z → + ∞ x ( z ) x(0) = \lim_{n \to 0}x(n) = \lim_{z \to +\infty}x(z) x(0)=limn→0?x(n)=limz→+∞?x(z)
x ( + ∞ ) = lim ? n → ∞ x ( n ) = lim ? z → 1 ( 1 ? z ? 1 ) x ( z ) x(+\infty) = \lim_{n \to \infty}x(n) = \lim_{z \to 1}(1-z^{-1})x(z) x(+∞)=limn→∞?x(n)=limz→1?(1?z?1)x(z)
?
x ( z ) = z ( z ? 1 2 ) ( z + 1 2 ) ( z + 1 4 ) x(z) = \frac{z(z-\frac{1}{2})}{(z+\frac{1}{2})(z+\frac{1}{4})} x(z)=(z+21?)(z+41?)z(z?21?)?
x ( z ) z = z ? 1 2 ( z + 1 2 ) ( z + 1 4 ) = 4 z + 1 2 ? 3 z + 1 4 \frac{x(z)}{z} = \frac{z-\frac{1}{2}}{(z+\frac{1}{2})(z+\frac{1}{4})}=\frac{4}{z+\frac{1}{2}}-\frac{3}{z+\frac{1}{4}} zx(z)?=(z+21?)(z+41?)z?21??=z+21?4??z+41?3?
x ( z ) = 4 z z + 1 2 ? 3 z z + 1 4 x(z) = \frac{4z}{z+\frac{1}{2}} - \frac{3z}{z+\frac{1}{4}} x(z)=z+21?4z??z+41?3z?
x ( n ) = 4 ( ? 1 2 ) n u ( n ) ? 3 ( ? 1 4 ) n u ( n ) x(n) = 4(-\frac{1}{2})^{n}u(n) -3 (-\frac{1}{4})^{n}u(n) x(n)=4(?21?)nu(n)?3(?41?)nu(n)
x ( z ) = 1 ( z ? 2 ) ( z ? 3 ) x(z) = \frac{1}{(z-2)(z-3)} x(z)=(z?2)(z?3)1?
1. z n ? 1 x ( z ) = z n ? 1 ( z ? 2 ) ( z ? 3 ) z^{n-1}x(z) = \frac{z^{n-1}}{(z-2)(z-3)} zn?1x(z)=(z?2)(z?3)zn?1?
2. R 1 = ( z ? 2 ) z n ? 1 ( z ? 2 ) ( z ? 3 ) ∣ z = 2 = ? 2 n ? 1 R_1 =(z-2)\frac{z^{n-1}}{(z-2)(z-3)}|_{z=2} = -2^{n-1} R1?=(z?2)(z?2)(z?3)zn?1?∣z=2?=?2n?1
3. R 2 = ( z ? 3 ) z n ? 1 ( z ? 2 ) ( z ? 3 ) ∣ z = 3 = 3 n ? 1 R_2 =(z-3)\frac{z^{n-1}}{(z-2)(z-3)}|_{z=3} = 3^{n-1} R2?=(z?3)(z?2)(z?3)zn?1?∣z=3?=3n?1
4. x ( n ) = ? 2 n ? 1 + 3 n ? 1 x(n) = -2^{n-1} + 3^{n-1} x(n)=?2n?1+3n?1
?
S = ∑ k = ? ∞ ∞ ∣ h ( n ) ∣ < + ∞ S=\sum_{k=-\infty}^{\infty}|h(n)| < +\infty S=∑k=?∞∞?∣h(n)∣<+∞